ANALISIS SISTEM PENGENDALIAN INTERN TERHADAP PEMBERIAN KREDIT PERUMAHAN RAKYAT (KPR) PADA PT. BANK TABUNGAN NEGARA (PERSERO) TBK. UNIT LUMBANJULU - FARIDA SAGALA (LP2MTBM MAKARIOZ, 2022)
Credit is a financial facility that allows a person or housing agency to borrow money to buy a product and pay it back over a period of time. In providing credit, a bank should carry out predetermined procedures and pay attention to the internal control system in the bank. Banks in collecting funds from the public rely on the principle of trust. The customer also keeps his money in the bank using the principle of trust that his money will not be misused by the bank in the hope that one day the customer's money will return. Banks repay the customer's trust by distributing funds back to customers, one of them with credit loans. Because of the importance of providing mortgages for PT Bank Tabungan Negara (Persero) Tbk, it is necessary to have good control from the housing management on the procedures for granting mortgage facilities the. The Internal Control System in the procedure for granting mortgages is very helpful for housing in avoiding the risk of non-performing loans (NPL) from an early stage in the provision of mortgage facilities. The internal control system is a process influenced by the board of directors, management and other personnel, designed to provide reasonable assurance about the achievement of objectives in the effectiveness and efficiency of operations, reliability of financial statements and compliance with applicable laws and regulations. The internal control system in the procedure for granting Public Housing Credit (KPR) does not depend on the number of stages passed by the prospective debtor, but rather on the stages that have been carried out properly and correctly.